Does student sampling impact our understanding of argumentativeness and verbal aggressiveness? - Croucher SM; Kelly S; Elers P; Jackson K; Nguyen T (Taylor and Francis Group on behalf of the American Forensic Association, 2024)
Student samples are regularly used in research. While student samples are convenient and easy to access, the use of such samples has been criticized for exposing theories and research to internal validity threats, as students are not representative of the general population. Using argumentativeness and verbal aggressiveness as contexts for analysis, this study explores the extent to which student and non-student samples differ in published empirical research. We found that in the case of the original verbal aggression and argumentativeness measures, sample type did not moderate the means among argumentativeness and verbal aggressiveness studies. We discuss the implications of these findings in terms of student vs. non-student samples.
Keywords: Sampling; validity; communication scales; argumentativeness; verbal aggressiveness